Long-term results after resection for gallbladder cancer. Implications for staging and management. - Bartlett, D L (1996)
BACKGROUND: The surgical management of gallbladder cancer is controversial. There is no consensus among surgeons as to the indications for reoperation or radical resection. OBJECTIVE: The purpose of this study was to examine results of reoperation after an incidental finding of gallbladder cancer after cholecystectomy, and results of radical resection in patients with advanced disease. METHODS: A retrospective review of 149 patients with the diagnosis of gallbladder cancer treated from 1985 to 1993 was performed. Fifty-eight patients were explored and 23 underwent resection for cure. Resection included trisegmentectomy in nine patients and bile duct resection in ten patients. Seventeen patients underwent re-exploration after an incidental finding of gallbladder cancer at initial cholecystectomy. RESULTS: Surgical resection is associated with an actuarial 51% 5-year disease-free survival rate, with a median follow-up time of 48 months. Eight patients are alive beyond 50 months. There were no operative deaths; the perioperative morbidity rate was 26%. Nodal status is the most powerful predictor of outcome. Two patients with T4, NO disease are alive without evidence of disease beyond 4 years. Thirteen of the 17 patients (76%) undergoing reoperation after simple cholecystectomy for T2 or T3 tumors had residual disease. CONCLUSIONS: Patients with nodal metastasis beyond the pericholedochal nodes should not be considered for curative resection. Tumors staged T4, NO should be included with stage III disease, and resection should be considered. Re-resection of T2 or T3 tumors after simple cholecystectomy is likely to include residual disease and should thus provide the only chance for long-term survival.